New Cytotoxic Tigliane Diterpenoids from Croton caudatus - Chen, Ying-Ying; Yang, Kun-Xian; Yang, Xing-Wei; Khan, Afsar; Liu, Lu; Wang, Bei; Zhao, Yun-Li; Liu, Ya-Ping; Li, Yan; Luo, Xiao-Dong (Planta Medica, 2016)
Three new tigliane-type diterpenoids were isolated from the methanolic extract of the twigs and leaves of Croton caudatus, trivially named crotusins A–C (1–3). The structures of compounds 1–3 were elucidated on the basis of extensive spectral methods. These new compounds were highly oxygenated and heavily substituted. Cytotoxic activity against five human tumor cell lines was assessed for compounds 1–3 of which compound 3 showed significant inhibitory activity with IC50 values ranging from 0.49 to 4.19 µM against these cells, while crotusins A and B exhibited moderate activity.
Keywords: Croton caudatus; Euphorbiaceae; tigliane diterpenoid; cytotoxic activity